RESPONSE OF LONKIDA (Nauclea orientalis L.) TOWARDS MYCORRHIZAL INOCULUM IN WATERLOGGED CONDITION - Faisal Danu Tuheteru; Cecep Kusmana; Irdika Mansur; Iskandar Iskandar (SEAMEO BIOTROP, 2015)
Waterlogged condition is one of the environmental stresses unfavorable for plants and mycorrhizal fungi. Arbuscular Mycorrhizal (AM) species that are tolerant tend to be more adaptive to waterlogged conditions. Besides increasing plant tolerance, the documented effects of AM fungi (AMF) inoculation on wetland plant performance remain inconsistent, and AMF application may also cause plant growth depression under waterlogging. This study aimed to examine the morpho-anatomical adaptation, survival, growth, biomass, and nutrient uptake of Nauclea orientalis (L.) seedlings from different habitats inoculated with Arbuscular Mycorrhizal Fungi under waterlogged conditions for 90 days. Experimental procedures included seed germination, preparation of AMF inoculum, inoculation, and waterlogging treatment. The results showed that N. orientalis seedlings formed lenticels (100%), adventitious roots (41%), and aerenchyma under waterlogged conditions. Seedlings originating from dryland habitats, both mycorrhizal and non-mycorrhizal, had lower height growth rate compared to those from other habitat types. Similar patterns were observed in relative growth rate for shoot (RGRs), root (RGRr), total (RGRt), and root-to-shoot ratio. Treatments of swamp habitat seedlings without waterlogging and with waterlogging, as well as savannah seedlings under waterlogged conditions, showed higher total plant dry weight and RGRt than other treatments. In general, total nitrogen concentration in roots and shoots was highest in the interaction between swamp habitat seedlings and non-mycorrhizal treatment under waterlogging. However, seedlings from dryland habitats required AMF under waterlogging to improve biomass and nitrogen accumulation in roots. Independently, waterlogging increased average height gain (18%), stem diameter (46%), leaf area (40%), leaf length (17%), and leaf width (21%). Nonetheless, waterlogged treatment decreased the number of leaves (9%) and AMF colonization (71%). The results indicate that seedlings from temporary swamp habitats demonstrated better growth performance and higher biomass under waterlogged conditions, regardless of AMF inoculation.